Agua como elemento de planeación urbana: Equipamiento de Educación y Desarrollo Ambiental - Pérez Mendoza, Deisy (Universidad de La Salle. Facultad de Ciencias del Hábitat. Arquitectura, 2017)
The Project share to integrate the main ecological structure with the urban dynamics that we find in Yopal to mitigate the environmental impacts, produced by the expropriation and the insufficient environmental education the population of Yopal has. This integration happens under an integral urban plan where an education and environmental equipment, works as a transition between the main elements of the ecological structure such as the Rio Cravo sur and the urban structure (Pontebedra neighborhood). It is strategically located on the north edge of the urban limits, creating spaces that allow develop integration for the urban dynamics, using spaces where the public think and trained to care natural setting. The project develops in two buildings, one of them characterized by the educational vocation, and the other where the cultural events happen to promote the full integration natural with the society.